Pemberdayaan Kelompok Tani Suka Maju, Desa Sambirejo, Kecamatan ambulu, Kabupaten Jember, Melalui Aplikasi Pupuk Organik Padat - R, Rizal (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Animal manure problems cause waste problems in the community. Solid organic fertilizer is an alternative solution for processing animal waste. The Mekar Sari Dua Farming Group in Ampel Village, Jember Regency has the potential to process solid organic fertilizer with one of the groups running a livestock farming business. The farmer  group  empowerment  program  through  the application  of  organic fertilizer using animal waste as a base material added with the biological agents tricoderma and PGPR resulted in an increase in farming income with a quality nutrient content of 1.531% N-Total, 1.268% P2O5, 2.125% K2O, and 8.380% C- Organic.